Hubungan Pengetahuan Ibu Mengenai Imunisasi Dasar Dengan Kepatuhan Imunisasi Bayi Usia 12 Bulan - Astuti, Etni Dwi; Nardina, Evita Aurilia (Bunda Edu-Midwifery Journal (BEMJ), 2020)
Background : In the 2012 IDHS, the basic immunization coverage rate in Indonesia has increased from year to year, in 2012 the BCG basic immunization coverage rate reached 89%, DPT immunization coverage reached 72%, polio 3 immunization coverage reached 76%, measles immunization reached 80% and complete basic immunization reaches 66%. From the results of interviews with mothers who immunized their babies at BPM Sri Farintina 60% immunized according to schedule and 40% did not go according to schedule. Knowledge and parental compliance are very important to achieve complete basic immunization fulfillment, especially midwives play an active role in providing immunization services. Research Objectives: To analyze the relationship between knowledge level and maternal compliance in providing basic immunization completeness at BPM Sri Farintina Gondangmanis Kudus. Research Methodology: The research method used in this research is correlation research method. The type of research used is analytical research, quantitative data types, using a cross sectional approach. The variables in this study were the mother's level of knowledge about basic immunization (independent variable) and infant immunization compliance (dependent variable). The sample in this study were 33 respondents who were taken by total sampling technique, the sample was taken from the data of mothers who had babies aged 12 months who immunized their babies at BPM Sri Farintina Gondangmanis Kudus. Results: From the results of this study, 21 respondents (63.64%) had good knowledge, while 15 respondents (45.5%) were obedient and 18 respondents (54.5%) were disobedient. Conclusion: There is no relationship between the level of maternal knowledge about basic immunization with immunization compliance for infants aged 12 months at BPM Sri Farintina Gondangmanis Kudus in 2018.